2022
DOI: 10.1021/acsenergylett.2c01749
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine Controlled Tin Perovskite Crystallization

Abstract: Controlling the crystallization of perovskite in a thin film is essential in making solar cells. Processing tin-based perovskite films from solution is challenging because of the uncontrollable faster crystallization of tin than the most used lead perovskite. The best performing devices are prepared by depositing perovskite from dimethyl sulfoxide because it slows down the assembly of the tin–iodine network that forms perovskite. However, while dimethyl sulfoxide seems the best solution to control the crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Reproduced with permission. [ 81 ] Copyright 2022, American Chemical Society. d) Schematic illustration: the effect of acetic acid (HAc) on regulation of crystallization kinetics and improvement of crystalline quality.…”
Section: Strategies For Suppressing Sn(ii)/sn(iv) Oxidation In Tpscsmentioning
confidence: 99%
“…Reproduced with permission. [ 81 ] Copyright 2022, American Chemical Society. d) Schematic illustration: the effect of acetic acid (HAc) on regulation of crystallization kinetics and improvement of crystalline quality.…”
Section: Strategies For Suppressing Sn(ii)/sn(iv) Oxidation In Tpscsmentioning
confidence: 99%
“…Numerous works have been devoted to enhancing the crystal quality of THPs by controlling the crystallization processes of THP films. For instance, Hao et al revealed that an intermediate solvate SnI 2 ·3DMSO could form to reduce the crystal growth rate of THPs when dimethyl sulfoxide (DMSO) was chosen as the solvent of a THP precursor solution . Jokar et al reported that the nucleation sites of THPs increased after introducing EDAI 2 in the FASnI 3 (FA: formamidinium) film, resulting in uniform and dense THP films .…”
mentioning
confidence: 99%
“…The competition of crystallization and reconstruction kinetics leads to poor-quality thin lms with visible pinholes and disordered crystal orientation, and to nal low-efficiency photovoltaic devices. 8,9 Currently, the highest reported photovoltaic efficiency based on 2D RP tin halide perovskite (n = 4) is 10.36%, 10 far lower than its Shockley-Queisser limit value (∼32%). 11 Several efforts have been made to control the crystallization process of RP tin-based perovskites via additives, [12][13][14] solvents, 15,16 and composition engineering.…”
Section: Introductionmentioning
confidence: 98%